FOREIGN INVESTMENT IN MONOPOLY PRACTICES IN THE MINING SECTOR - Setyarini Nur Octaviana (UNTAG Law Review, 2021)
In Indonesia, Joint Venture is regulated in Law No. 25 of 2007 onInvestment. Joint Venture itself is a form of alliance that emphasizes more on cooperation and its temporary nature. Before the occurrence of Joint Venture in the establishment of the company conducted a Joint Venture agreement, it contains the agreement of both parties. Law No. 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition regulates the prohibition of a company in carrying out its business activities, must not do 3 things, namely: make a prohibitedagreement, become the dominant position, and conduct prohibited activities. On the contrary, Law No. 40 of 2007 on Limited Liability Companies and also Law No. 25 of 2007 on Investment does not regulate the matter. Therefore the company does it by joint venture. The company's growth in the mining sector is growing very rapidly. To attract investors, the government is expanding in the mining sector. Certainly in this case the practice of monopoly in a company is very likely to occur as mining sector companies increase. The research method used by the author is normative juridical, i.e. research whose reference material uses the norms contained in the laws and regulations. The results showed that companies have implications for monopoly practices, of course a company, especially the mining sector, should also consider the principle of fairness.